Začetek in konec raziskovanj grobišča pri Župni cerkvi v Kranju (1953 in 2011−2013) = The beginnning and end of exploration at the Župna cerkev cemetery in Kranj (1953 and 2011−2013) - Pleterski, Andrej (Opera Instituti Archaeologici Sloveniae;Grobišče Župna cerkev v Kranju, 2019)
It was in the spring of 1953 when digging pits to plant trees in front of the Prešeren's Theatre in Kranj revealed some graves. Extensive excavations followed, led by Jože Kastelic and Vinko Šribar from the National Museum. 308 graves were excavated: 15 were recognised as the so-called (later) "Baroque" graves and 293 as "Ketlach", that is Early Medieval ones. The finds were first stored in the National Museum in Ljubljana, and later moved to the Gorenjski museum in Kranj, while all the documentation remained in Ljubljana.